Does bicycling contribute to erectile dysfunction? Examining the evidence - Brant, W. O.; Lue, T. F.; Smith, J. F. (The Physician and Sportsmedicine, 2009)
Abstract: Bicycling is a popular means of recreation, transport, and fitness training for many people around the world, but questions have been raised about its threat to sexual function. This review summarizes some of the data on whether cycling is or is not an independent risk factor for erectile dysfunction and other sexual complaints. Space limitations will confine our discussion to men, although these problems are also important in women.